Atomic mobility in calcium and sodium aluminosilicate melts at 1200 °C. (1st November 2016) - Claireaux, Corinne; Chopinet, Marie-Hélène; Burov, Ekaterina; Gouillart, Emmanuelle; Roskosz, Mathieu; Toplis, Michael J.
Abstract: Multicomponent chemical diffusion in liquids of the quaternary system CaO–Na2 O–Al2 O3 –SiO2 has been studied. Diffusion-couple experiments were performed at 1200 °C and for different durations around a central composition of 64.5 wt%SiO2, 13.3 wt%Na2 O, 10.8 wt%CaO, 11.4 wt%Al2 O3, leading to an overconstrained system of equations that was used to determine the diffusion matrix of the system. The dominant eigenvector of the diffusion matrix was found to correspond to the exchange between sodium and calcium, consistent with the results of the ternary soda–lime silica system. On the other hand, neither of the other two eigenvectors of the diffusion matrix of the quaternary system involve sodium. Given a factor of 50 between the dominant and second eigenvalue, diffusion couples involving the exchange of sodium oxide and a network-forming oxide result in strong uphill diffusion of calcium. The second eigenvector, corresponding to the exchange of calcium with silicon and aluminum, is close to the dominant eigenvector found in previous studies of ternary alkaline-earth aluminosilicate systems. Our results therefore suggest that simple systems may be used to understand diffusive mechanisms in more complex systems.